Short Communication: Morphological study of Fagraea ceilanica (Gentianaceae) in Mount Nglanggeran, Yogyakarta, Indonesia - WIDODO WIDODO; MUHAMMAD JA’FAR LUTHFI (Society for Indonesian Biodiversity, 2016)
Widodo, Luthfi MJ. 2016. Morphological study of Fagraea ceilanica (Gentianaceae) in Mount Nglanggeran, Yogyakarta, Indonesia. Biodiversitas 17: 454-460. Fagraea ceilanica Thunb. population were found in the Mount Nglanggeran in Gunungkidul, Yogyakarta, Indonesia. Identification was based on the literature and herbarium specimens. The study was conducted through continued exploration and examination on specimen collection. The existence of F. ceilanica in Java was only described in Flora of Java by Backer and Bakuizen van den Brink (1965). Fagraea ceilanica is a liana climbing on large stone. Characteristic for initial identification were ovate to ellipsoid leaves which were opposite, thick and grayish green; bell-trumpet flower shape with flowering season around March and whitish to yellowish color and also 5-8 cm corolla tube. This paper presents important morphological character, namely leaves, stems, flowers, and fruits of F. ceilanica. Study on morphological character of F. ceilanica found on Mount Nglanggeran is needed to recognize its potential, benefit and conservation of this species.